Linearization of donor DNA during plasmid transformation in Neisseria gonorrhoeae. - Biswas, G D (1986)
We examined the fate of plasmid DNA after uptake during transformation in Neisseria gonorrhoeae. An 11.5-kilobase plasmid, pFA10, was processed to linear double-stranded DNA during uptake by competent cells, but cleavage of pFA10 was not site specific. A minority of pFA10 entered as open circles. A 42-kilobase plasmid, pFA14, was degraded into small fragments during uptake; no intracellular circular forms of pFA14 were evident. Since pFA10 DNA linearized by a restriction enzyme was not further cut during uptake, the endonucleolytic activity associated with entry of plasmid DNA appeared to act preferentially on circular DNA. Although linear plasmid DNA was taken up into a DNase-resistant state as efficiently as circular DNA, linear plasmid DNA transformed much less efficiently than circular plasmid DNA. These data suggest that during entry transforming plasmid DNA often is processed to double-stranded linear molecules; transformants may arise when some molecules are repaired to form circles. Occasional molecules which enter as intact circles may also lead to transformants.